2020
DOI: 10.1155/2020/8130760
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Changes of Mumps Characteristics with Different Vaccination Strategies Using Surveillance Data: Importance to Introduce the 2-Dose Schedule in Quzhou of China

Abstract: Background. From 2005 to 2016, the prevention and control of mumps in China have undergone three stages of transition. These include the use of MuCV as a self-supported vaccine, the introduction of one-dose MMR to the Expanded Program on Immunization (EPI), and the administration of two-dose MuCV following supplementary immunization activities (SIAs) using MM. Here, using surveillance data, we assessed the epidemiology of mumps during the three stages. Methods. Children in Quzhou of China born from 2005 to 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…In practice, although the EPI-MMR was introduced in Guangzhou in September 2008, the number of mumps cases was not brought under control quickly and effectively. After a few years, it began to display a downward trend, similar to the situation observed in the whole of China, and in some other cities [ 28 , 29 , 30 , 31 ]. The reason for this is that from 2008–2011, only children aged 2–5 years were the target population of the EPI, while all children above five years are at high risk of mumps.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In practice, although the EPI-MMR was introduced in Guangzhou in September 2008, the number of mumps cases was not brought under control quickly and effectively. After a few years, it began to display a downward trend, similar to the situation observed in the whole of China, and in some other cities [ 28 , 29 , 30 , 31 ]. The reason for this is that from 2008–2011, only children aged 2–5 years were the target population of the EPI, while all children above five years are at high risk of mumps.…”
Section: Discussionsupporting
confidence: 72%
“…Some descriptive epidemiological approaches indicated the effectiveness of the EPI-MMR, although they failed to accurately quantify the effect of the intervention [ 30 , 31 , 33 ]. Some studies offered a third dose of MMR vaccine to some eligible students and calculated mumps incidence rates for specific periods, before and after the intervention [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the effectiveness of single-dose MMR vaccine is not so ideal. Several studies have reported that the protective effect of MuCV diminishes over time and declines rapidly by the 5th year after vaccination [ 38 , 39 ]. It may be the comprehensive reasons of these economic, meteorological and, vaccine factors that explain the northward movement of mumps hotspot clusters.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Despite the high vaccination rate of MMR in Quzhou, 8,525 mumps cases were reported from 2005 to 2016, with more than 1,839 mumps cases reported in 2009. 7 From September to December in 2010, supplementary immunization activity (SIA) using measles mumps (MM) was performed in Zhejiang province. The children born from 1 October 2005 to 31 December 2009 would receive one dose of MM free of charge, whether they were local or migrant children, and with or without a history of MuCV.…”
Section: Introductionmentioning
confidence: 99%